2015
DOI: 10.1177/0044118x15617401
|View full text |Cite
|
Sign up to set email alerts
|

Old Wine, New Bottle? Comparing Interpersonal Bullying and Cyberbullying Victimization

Abstract: This study uses a large nationally representative sample to compare and contrast interpersonal bullying and cyberbullying by asking the following questions: (a) How does the prevalence of cyberbullying victimization compare with the prevalence of interpersonal bullying victimization? (b) How does the relationship between demographic predictors and cyberbullying victimization compare with the relationship between these predictors and interpersonal bullying victimization? and (c) How does the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 100 publications
3
31
0
Order By: Relevance
“…Ortega- Barón et al (2016) have shown that victims of moderate to severe cyberbullying have significantly lower academic self-esteem than non-victimized adolescents, as well as a significantly lower sense of peer affiliation. In fact, as highlighted by Payne and Hutzell (2017), victims of any form of bullying are prone to avoidance behaviors towards school settings compared to students who have not experienced such victimization.…”
Section: Introductionmentioning
confidence: 99%
“…Ortega- Barón et al (2016) have shown that victims of moderate to severe cyberbullying have significantly lower academic self-esteem than non-victimized adolescents, as well as a significantly lower sense of peer affiliation. In fact, as highlighted by Payne and Hutzell (2017), victims of any form of bullying are prone to avoidance behaviors towards school settings compared to students who have not experienced such victimization.…”
Section: Introductionmentioning
confidence: 99%
“…The main purpose of these studies was to design preventive, analytical and intervention instruments for bullying/cyberbullying (Del Rey et al, 2012; Allison and Kirsten, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…As a result of the negative psychological and academic problems associated with bullying, policymakers and school officials have developed a keen interest in the topic. Not only does bullying pose problems for schools (Payne & Hutzell, 2017), its impact may even stretch to intergenerational transmission. In a recent study, boys who were said to have bullied at age 14 were more likely at age 32 to have their own sons become bullies (Ttofi & Farrington, 2012).…”
Section: Bullyingmentioning
confidence: 99%
“…Social-Emotional Impact. Though a very small percentage of cyberbully victims experience suicide ideation, victims from multiple studies reported significant health and social problems which have included anger, social anxiety, despair, higher levels of depression, lower self-esteem, headaches, academic problems, drug and alcohol addiction, pedagogical problems for teachers, and higher rates of absenteeism (DePaolis & Williford 2014;Eden, Heiman, & Olenick-Shemesh, 2013;Kowalski & Limber, 2012;Navarro, Ruiz-Oliva, Larrañaga & Yubero, 2013;Navarro & Jasinski, 2013;Payne & Hutzell, 2017). Other research has underscored the notion that the more severe an adolescent is bullied, the more likely that individual will experience mental health and social issues, as well as display low academic achievement and psychosocial problems (Tokunaga, 2010).…”
Section: Imbalance Of Powermentioning
confidence: 99%
See 1 more Smart Citation